To receive graciously but stock prudently: the ift and exchange programme of the University of Malaya library - Lim, S.H. (University of Malaya Library, 1990)
The University of Malaya has a healthy gift and exchange programme through which gifts received from individuals and organizations have enriched existing collections and made available to the academic community specialized materials, which could never have been acquired through the normal booktrade. The exchange programme has helped in the acquisitions of valuable research reports and scholarly publications, which are not made available for purchase.